2018
DOI: 10.1002/anie.201806035
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Photoswitchable α/β Peptides toward Two‐State Foldamers

Abstract: A simple, unsaturated, E-Z photoisomerizable β-amino acid, (Z)-3-aminoprop-2-enoic acid, has been introduced into peptide foldamers through a one-pot chemical coupling, based on Pd/Cu-catalyzed olefin oxidative amidation, between two peptide segments carrying, respectively, a -Gly-NH residue at the C-terminus and an acryloyl group at the N-terminus. Reversible conversion between the Z and E configurations of the 3-aminoprop-2-enoic linkage was achieved photochemically. A crystallographic analysis on two model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It has been found that Aaa (Δ Z βAla) residue in a peptide allows formation of an N-H••O = C intra-residue H-bond which closes a 6-membered pseudo ring system, allowing the peptide to form a well-de ned 3D architecture of the attened β sheet 29 . Recent studies demonstrated that foldamers containing Δ Z βAla/Δ E βAla units display interesting conformational, electronic, and supramolecular aggregation properties that can be modulated by selective E-Z photoisomerization [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that Aaa (Δ Z βAla) residue in a peptide allows formation of an N-H••O = C intra-residue H-bond which closes a 6-membered pseudo ring system, allowing the peptide to form a well-de ned 3D architecture of the attened β sheet 29 . Recent studies demonstrated that foldamers containing Δ Z βAla/Δ E βAla units display interesting conformational, electronic, and supramolecular aggregation properties that can be modulated by selective E-Z photoisomerization [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Photoswitchable α–Δβ foldamers containing single [ 248 ] or multiple (up to four) units of Δ Z β-Ala (( Z )-3-aminoprop-2-enoic acid, the C α,β -unsaturated analog of β-Ala) [ 249 ] were studied in water and acetonitrile, respectively. The singly Δ Z β-Ala-substituted peptide Cbz-(Ala-Aib) 2 -Ala-Gly-Δ Z β-Ala-Lys-Leu-Val-Phe-Phe-OH was irradiated at 290–320 nm in water, and the stable hydrogel was submitted to TEM analysis with uranyl acetate staining.…”
Section: Foldamers Based On Other Building Blocksmentioning
confidence: 99%
“…On the contrary, in the Z isomer, the intraresidue N-H···O=C interaction of Δ Z β-Ala, experimentally demonstrated by single-crystal XRD and 1 H NMR in CD 3 CN solution, simultaneously led to the loss of two potential intermolecular hydrogen bonds and to a bent overall structure, for which no higher aggregations of dimers should be possible. In fact, after 10 min irradiation at 254 nm of hydrogel containing 95% E isomer, the equilibration to a 6:4 E / Z mixture led to an almost complete fiber dissociation and hydrogel destruction [ 248 ].…”
Section: Foldamers Based On Other Building Blocksmentioning
confidence: 99%
“…Foldamer structures allow chemists to broaden and expand the limited range of structural components that body up natural proteins, and foldamers have been designed to carry out protein‐like functions of binding, catalysis and signal relay [22] . We recently succeeded in introducing the simplest unsaturated ( E ‐ Z photoisomerizable) β‐amino acid, namely ( Z )‐3‐aminoprop‐2‐enoic acid (Δ Z βAla), into peptide foldamers [23, 24] . The reversible conversion between the Δ Z βAla and Δ E βAla configurations, achieved photochemically, was accompanied by remarkable consequences on the 3D‐structure of the peptides.…”
Section: Figurementioning
confidence: 99%
“…[22] We recently succeeded in introducing the simplest unsaturated (E-Z photoisomerizable) b-amino acid, namely (Z)-3-aminoprop-2-enoic acid (D Z bAla), into peptide foldamers. [23,24] The reversible conversion between the D Z bAla and D E bAla configurations, achieved photochemically, was accompanied by remarkable consequences on the 3D-structure of the peptides. This allowed their molecular self-association through intermolecular hydrogen bonding to be spatiotemporally turned on-off.…”
mentioning
confidence: 99%